The ecology of money - Douthwaite, Richard (Green books for the Schumacher Society, 1999)
The book introduces much needed clarity in the domain of money. The answers of 6 questions used to describe reader through different money systems, a process which facilitates comparisons of the nature, advantages and disadvantages of each money system that the author describes.